Clinical, echocardiographic and haemodynamic predictors of morbidity and mortality in pulmonary hypertension: a nation-wide registry - Akbulut, M.; Kaymaz, C.; Basarici, I; Yildirimturk, O.; Asker, M.; Yaylali, T.; Tokgozoglu, L. (Oxford Univ Press, 2024)
[Abstract Not Available]
European-Society-of-Cardiology Congress (ESC) -- AUG 30-SEP 02, 2024 -- London, ENGLAND